2018
DOI: 10.3389/fpsyg.2017.02303
|View full text |Cite
|
Sign up to set email alerts
|

Improved Digit Span in Children after a 6-Week Intervention of Playing a Musical Instrument: An Exploratory Randomized Controlled Trial

Abstract: Previous studies have reported that music training not only improves children's musical skills, but also enhances their cognitive functions. However, there is a disagreement about what domain(s) might be affected. Moreover, effects of short-term ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 43 publications
3
47
1
5
Order By: Relevance
“…It is also important to note that several cognitive functions tested in the present study did not benefit from music training (auditory attention, visuomotor precision). For instance, in contrast to the results of Guo and colleagues [26] showing significant improvement in backward Digit Span scores after only 6 weeks of musical training, we did not find similar improvements of working memory. While the reasons for such variability in the results are difficult to determine, the question of whether music training has a general impact on cognitive abilities or whether its influence is specific to cognitive functions that share common processes with music, such as language for instance, is still an open issue [19,20,5961].…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…It is also important to note that several cognitive functions tested in the present study did not benefit from music training (auditory attention, visuomotor precision). For instance, in contrast to the results of Guo and colleagues [26] showing significant improvement in backward Digit Span scores after only 6 weeks of musical training, we did not find similar improvements of working memory. While the reasons for such variability in the results are difficult to determine, the question of whether music training has a general impact on cognitive abilities or whether its influence is specific to cognitive functions that share common processes with music, such as language for instance, is still an open issue [19,20,5961].…”
Section: Resultscontrasting
confidence: 99%
“…Moreover, results of cross-sectional studies in children have shown that music training is associated with better working and short-term memory as reflected by higher scores at the backward and forward versions of the Digit Span test (i.e., repeat back series of orally presented numbers) in musically-trained compared to untrained children [3,25]. Very recently, Guo and collaborators [26] provided evidence for a causal link between music training and working memory in an interventional study: children quasi-randomly assigned to six weeks of music training increased their backward digit span scores but the forward digit span scores did not differ between the music and control groups. Moreover, Degé and collaborators [27] used a longitudinal approach and showed that children trained in music for two years improved visual and auditory memory (recalling sequences of colors or sounds), while their non-trained counterparts did not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a longitudinal study of 6-8-year-old children, half of the sample was randomly assigned to biweekly keyboard training for 6 weeks, while the other half received no training. Afterward, only the training group demonstrated a significant improvement in working memory capacity, measured with the backward digit span task (Guo et al, 2018). Advantages in working memory capacity have also been observed in school-aged children who received at least 6 months of music lessons (Degé and Schwarzer, 2017), as well as pre-schoolers who received 1 year of violin instruction (Fujioka et al, 2006).…”
Section: Relationships Between Music Training and Working Memory In Cmentioning
confidence: 88%
“…Alternatively, music training may cause enhancement of cognitive abilities. Longitudinal studies in which participants were randomly assigned to music training or control conditions clearly indicate a causal effect of training on working memory capacity (Fujioka et al, 2006;Degé and Schwarzer, 2017;Guo et al, 2018). Furthermore, evidence for a dose-response relationship between musical practice and working memory supports the view that training, rather than any predisposition, produces changes in working memory capacity (Bergman Nutley et al, 2014).…”
Section: Relationships Between Music Training and Working Memory In Cmentioning
confidence: 91%